Determination of the compressive modulus of elasticity of periodontal ligament derived from human first premolars - Nuttapol Limjeerajarus; Pimpet Sratong-on; Phetcharat Dhammayannarangsi; Kevin A. Tompkins; Paksinee Kamolratanakul; Krisadi Phannarus; Thanaphum Osathanon; Chalida Nakalekha Limjeerajarus (Heliyon, 2023)
Purpose: There are two commonly cited modulus of elasticity of the human periodontal ligament (EPDL), i.e., 6.89 ✕ 10−5 GPa (E1) and 6.89 ✕ 10−2 GPa (E2), which are exactly 1000-fold different from each other. This study aims to clarify the ambiguity of the two EPDL used for simulations and determine a more accurate EPDL value of human first premolars using experimental and simulation approaches. Methods: Numerical simulations using finite element analysis were performed to analyze PDL deformation under an average Asian occlusal force. To confirm the results, simple and multi-component, true-scale 3D models of a human first premolar were used in the simulations. Finally, a compression test using a universal testing machine on PDL specimens was conducted to identify the compressive EPDL of human first premolars. Results: The simulation results from both models revealed that E1 was inaccurate, because it resulted in excessive PDL deformation under the average occlusal force, which should not occur during mastication. Although the E2 did not lead to excessive PDL deformation, it was obtained by an error in unit conversion with no scientific backing. In contrast, the compression test results indicated that the compressive EPDL was 9.64 ✕ 10−4 GPa (E3). In the simulation, E3 did not cause excessive PDL deformation. Conclusion: The simulation results demonstrated that both commonly cited EPDL values (E1 and E2) were incorrect. Based on the experimental and simulation results, the average compressive EPDL of 9.64 ✕ 10−4 GPa is proposed as a more accurate value for human first premolars. Clinical significance: The proposed more accurate EPDL would contribute to more precise and reliable FEA simulation results and provide a better understanding of the stress distribution and deformation of dental materials, which will be beneficial to precision dentistry, orthodontics and restoration designs.